2019
DOI: 10.1039/c8dt05087b
|View full text |Cite
|
Sign up to set email alerts
|

Loading Co3N nanoparticles as efficient cocatalysts over Zn0.5Cd0.5S for enhanced H2 evolution under visible light

Abstract: Co3N nanoparticles were decorated on Cd0.5Zn0.5S as highly efficient co-catalysts via a facile method. The H2 evolution activity of Co3N(2 wt%)/Cd0.5Zn0.5S is 25 times higher than that of pure Cd0.5Zn0.5S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Cobalt‐based nitride is also a type of promising co‐catalyst which is a noble metal substitute for photocatalytic applications. [ 169 ] Chen et al. reported that Co 3 N can be synthesized and used as a cocatalyst for enhanced photocatalytic H 2 production (≈137.33 mmol g –1 h –1 ) and apparent quantum yield (≈14.9% at 450 nm) in water based on CdS nanorods.…”
Section: Application Of Tmns In Photocatalysismentioning
confidence: 99%
See 4 more Smart Citations
“…Cobalt‐based nitride is also a type of promising co‐catalyst which is a noble metal substitute for photocatalytic applications. [ 169 ] Chen et al. reported that Co 3 N can be synthesized and used as a cocatalyst for enhanced photocatalytic H 2 production (≈137.33 mmol g –1 h –1 ) and apparent quantum yield (≈14.9% at 450 nm) in water based on CdS nanorods.…”
Section: Application Of Tmns In Photocatalysismentioning
confidence: 99%
“…The photo‐generated electrons can be efficiently excited from the CB of the semiconductor to the surface of Co 3 N, thereby effectively separating the photoexcited hole pairs ( Figure a). [ 169 ] In addition, Co 3 N and semiconductor photocatalyst have tightly combined to form a tight metal‐semiconductor interface, thus also improving the electron transport efficiency. Thus, we can conclude that Co 3 N could collect and transport electrons to extend the carrier lifetimes and improve photocatalytic activity.…”
Section: Application Of Tmns In Photocatalysismentioning
confidence: 99%
See 3 more Smart Citations